Is religiosity a good predictor of psychological health in patients undergoing major lower limb amputations? - Ang Poh Thean, Charles; Awang, Shukrimi; Musa, Ramli; Karupiah, Rajandra Kumar; Zakaria@Mohamad, Zamzuri (2020)
INTRODUCTION: Major lower limb amputation has a huge psychological impact on the patient and has been a concern to treating surgeons. Like with all other medical conditions, prevention is better than cure. Thereby it is of uttermost importance to identify susceptible individuals and early referral to the relevant department to minimize the suffering of these individuals. The aim of this study is to determine if religiosity is associated with psychological health in individuals undergoing major lower limb amputation. MATERIALS AND METHODS: This is a single centre prospective cross sectional observational study involving fifty patients seen in the outpatient department who has undergone a major lower limb amputation (above knee or below knee amputation) in the past two years. They were assessed based on Depression Anxiety Stress Scale- 21 (DASS- 21), Rosenberg Self Esteem Scale and The Duke University Religion Index (DUREL). RESULTS: Final results show that there is a significant difference between the intrinsic religiosity (IR) component of DUREL with the depression (P-value 0.001) and anxiety (P-value 0.011) component of DASS. A collective data from this study shows that these individuals suffers more from anxiety rather than depression, stress or low self- esteem. This information is an important aspect to look into, as relevant parties can do the necessary to reduce the anxiety faced by these individuals. CONCLUSION: The conclusion from this study suggest that individuals with low intrinsic religiosity are more likely to suffer from depression and anxiety following a major lower limb amputation.